A dipole on the sky: predictions for hypervelocity stars from the Large Magellanic Cloud - Boubert, D; Evans, N (American Astronomical Society, 2016)
We predict the distribution of hypervelocity stars (HVSs) ejected from the Large Magellanic Cloud (LMC), under the assumption that the dwarf galaxy hosts a central massive black hole (MBH). For the majority of stars ejected from the LMC, the orbital velocity of the LMC has contributed a significant fraction of their galactic rest-frame velocity, leading to a dipole density distribution on the sky. We quantify the dipole using spherical harmonic analysis and contrast with the monopole expected for HVSs ejected from the Galactic center (GC). There is a tendril in the density distribution that leads the LMC, which is coincident with the well-known and unexplained clustering of HVSs in the constellations of Leo and Sextans. Our model is falsifiable since it predicts that Gaia will reveal a large density of HVSs in the southern hemisphere.